â€œMen Do Not Talkâ€: Hegemonic Masculinity and the Practice of Emotional Suppression - Erdin Prayoga; Ika Arinia Indriyany (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Â This study aims to analyze the phenomenon of â€œmen do not talkâ€ through the perspective of hegemonic masculinity theory and to explain how masculinity norms influence menâ€™s emotional expression and help-seeking behavior. This research uses a qualitative approach with a literature review method. The research instrument consists of scientific documents including journal articles and academic books related to masculinity and menâ€™s mental health. Data were collected through academic databases such as PubMed, Scopus, Web of Science, PsycINFO, and Google Scholar. Data analysis was conducted using thematic meta-synthesis to identify and interpret the main themes found in the literature. The findings indicate that menâ€™s emotional silence is closely related to masculinity norms emphasizing strength and emotional control. These norms often lead men to suppress emotional expression and avoid seeking professional help. However, recent studies also show the emergence of more inclusive forms of masculinity that encourage emotional openness and help-seeking.